Evaluating human cancer cell metastasis in zebrafish - Teng, Yong (BioMed Central, 2013)
BACKGROUND: In vivo metastasis assays have traditionally been performed in mice, but the process is inefficient and costly. However, since zebrafish do not develop an adaptive immune system until 14 days post-fertilization, human cancer cells can survive and metastasize when transplanted into zebrafish larvae. Despite isolated reports, there has been no systematic evaluation of the robustness of this system to date. METHODS: Individual cell lines were stained with CM-Dil and injected into the perivitelline space of 2-day old zebrafish larvae. After 2-4 days fish were imaged using confocal microscopy and the number of metastatic cells was determined using Fiji software. RESULTS: To determine whether zebrafish can faithfully report metastatic potential in human cancer cells, we injected a series of cells with different metastatic potential into the perivitelline space of 2 day old embryos. Using cells from breast, prostate, colon and pancreas we demonstrated that the degree of cell metastasis in fish is proportional to their invasion potential in vitro. Highly metastatic cells such as MDA231, DU145, SW620 and ASPC-1 are seen in the vasculature and throughout the body of the fish after only 24–48 hours. Importantly, cells that are not invasive in vitro such as T47D, LNCaP and HT29 do not metastasize in fish. Inactivation of JAK1/2 in fibrosarcoma cells leads to loss of invasion in vitro and metastasis in vivo, and in zebrafish these cells show limited spread throughout the zebrafish body compared with the highly metastatic parental cells. Further, knockdown of WASF3 in DU145 cells which leads to loss of invasion in vitro and metastasis in vivo also results in suppression of metastasis in zebrafish. In a cancer progression model involving normal MCF10A breast epithelial cells, the degree of invasion/metastasis in vitro and in mice is mirrored in zebrafish. Using a modified version of Fiji software, it is possible to quantify individual metastatic cells in the transparent larvae to correlate with invasion potential. We also demonstrate, using lung cancers, that the zebrafish model can evaluate the metastatic ability of cancer cells isolated from primary tumors. CONCLUSIONS: The zebrafish model described here offers a rapid, robust, and inexpensive means of evaluating the metastatic potential of human cancer cells. Using this model it is possible to critically evaluate whether genetic manipulation of signaling pathways affects metastasis and whether primary tumors contain metastatic cells.